2018
DOI: 10.2147/ijn.s152822
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedical studies of the restoration of nitric oxide/peroxynitrite balance in dysfunctional endothelium by 1,25-dihydroxy vitamin D<sub>3</sub> &ndash; clinical implications for cardiovascular diseases

Abstract: Background Clinical studies indicate that vitamin D 3 improves circulation and may have beneficial effects in hypertension. This study uses nanomedical systems to investigate the role of 1,25-dihydroxy vitamin D 3 in the preservation/restoration of endothelial function in an angiotensin II (Ang II) cellular model of hypertension. Methods 1,25-dihydroxy vitamin D 3 -stimulated nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…In agreement with this study, Noris and his colleagues [ 38 ] demonstrated an excess formation of ONOO − in a preeclamptic placenta. ONOO − formation does not only inactivate NO ∙ but also leads to uncoupling of eNOS [ 39 ]. Uncoupled eNOS generates O 2 ·− rather than NO ∙ [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this study, Noris and his colleagues [ 38 ] demonstrated an excess formation of ONOO − in a preeclamptic placenta. ONOO − formation does not only inactivate NO ∙ but also leads to uncoupling of eNOS [ 39 ]. Uncoupled eNOS generates O 2 ·− rather than NO ∙ [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of rutin to reduce the AOPP level was highly comparable to that of lisinopril. The inhibition of eNOS with production of peroxynitrite (ONOO‐) which is a cytotoxic molecule could also aggravate the formation of AOPP, thereby fostering endothelial damage and ultimate cardiovascular system compromise (Khan et al., 2018). The production of ONOO‐ is from the reaction between the superoxide anion radical (O 2 • ‐ ) and NO, with concomitant reduction in the NO bioavailability, thereby precipitating hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…If [NO]/[ONOO -] falls below 0.5, it produces a severe oxidative stress that contributes to mechanisms of disease. 24 We found that it is not the absolute level of NO or ONOO -, but the ratio between them that is the determinant of the cellular redox environment (Burewicz et al, 2013;Mason et al, 2015;Khan et al, 2018;Sambe et al, 2018).…”
Section: Discussionmentioning
confidence: 81%